Investigation on stability and viscosity of SiO2–CH3OH (methanol) nanofluids. (March 2016) - Mostafizur, R.M.; Abdul Aziz, A.R.; Saidur, R.; Bhuiyan, M.H.U.
Abstract: This work studied the stability and viscosity of methanol based nanofluids with SiO2 nanoparticles at various volume concentrations and temperatures in order to investigate the enhancement in heat transfer. SiO2 nanoparticles of 5 ~ 15 nm sizes were suspended into methanol base fluid at five different concentrations which were 0.005, 0.01, 0.05, 0.10 and 0.15 vol%. The nanofluid preparation was completed through sonication using an ultrasonic homogenizer. The viscosity of the prepared nanofluids was measured by LVDV III ultra-programmable viscometer at five different temperatures (5, 10, 15, 20 and 25 °C). The measurement deviations were about 3.96% and 2.4% for pure methanol and water, respectively. The results of zeta potential and UV-Vis spectrometer showed that SiO2 –methanol nanofluids were stable. It was found that shear stress and viscosity increased with volume concentration and shear rate and decreased in terms of temperature. These results showed that SiO2 –methanol nanofluids appeared as a non-Newtonian fluid. The maximum viscosity increment was 13.5% at 0.15 vol% base fluid and temperature of 25 °C. Therefore, this study revealed that viscosity enhancement depends on both volume concentration and temperature.